A type 2 immune circuit and arachidonic acid metabolism role in anti-nematode infection: evidence from transcriptome and targeted metabolome data in goat - W.X. Chen; Q.X. Yan; R.Z. Zhong; S.X. Tang; J.J. Loor; Z.L. Tan (Animal)
The gastrointestinal nematode infection poses a covert threat to both humans and domestic animals worldwide, eliciting a type 2 immune response within the small intestine. Intestinal tuft cells detect the nematode and activated group 2 innate lymphoid cells. Tuft cell−derived leukotrienes (one of the metabolites of arachidonic acid) were found to drive rapid anti-helminth immunity, but it is still poorly understood whether the tuft cell−mediated type 2 immune circuit and arachidonic acid metabolism modulate anti-parasitic immunity in the gastric epithelium. This study was designed to evaluate the immunological responses of goats inoculated with or without H. contortus. Results showed that H. contortus infection induced a systemic type 2 immune response, characterised by lymphocyte proliferation and greater eosinophils both in peripheral blood and abomasal mucosa, as well as increased type 2 cytokines IL-4, IL-5, and IL-13. Infection of H. contortus altered the transcriptome of the abomasum epithelium, especially tuft cell−mediated circuit-key genes. The infection also influenced the abomasal microbiota, arachidonic acid metabolism and related lipid metabolites, accompanying with great increases in the secretion of leukotrienes and prostaglandins. These findings demonstrate the role of tuft cells mediated circuit in sensing H. contortus infection and immune activation, reveal the candidate function of arachidonic acid involved in anti-helminth immunity, and suggest novel strategies for the control of parasitic diseases in livestock and humans.